High‐frequency InAlN/GaN HFET with fmax over 400 GHz. Issue 12 (1st June 2018) - Fu, Xing‐Chang; Lv, Yuanjie; Zhang, Li‐Jiang; Zhang, Tong; Li, Xian‐Jie; Song, Xubo; Zhang, Zhirong; Fang, Yulong; Feng, Zhihong
Abstract : Ultra‐thin InAlN/GaN heterostructure field‐effect transistors (HFETs) having high maximum oscillation frequency ( f max ) are fabricated by scaling lateral dimensions. A 3 nm GaN cap layer is adopted to reduce the electron density and suppress the short‐channel effects. Non‐alloyed regrown n + ‐GaN ohmic contacts with total ohmic resistance ( R tot ) of 0.13 Ω.mm is also introduced into the device, in which the virtual source‐to‐drain distance is 600 nm. T‐shaped gate with 40 nm length is formed in the centre of the source‐to‐drain region by self‐aligned e‐beam lithography. The peak extrinsic transconductance ( g m ) reaches 956 mS/mm. Most of all, a high f max of 405 GHz is obtained, which is the highest value among the reported InAlN/GaN HFETs. These obtained results mean that the InAlN/GaN HFETs having reliability should be still suitable for G‐band (140–220 GHz) power‐amplifier application with further optimisation.